PERUBAHAN PENUTUPAN LAHAN DAN PENGARUHNYA TERHADAP CADANGAN AIR PADA DAERAH TANGKAPAN AIR DANAU DUSUN BESAR - Suhardi Suhardi (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2005)
The aim of this research was to determine the change of regions covered by vegetation in catchment area of Dusun Besar Lake. The research was conducted by analyzing Landsat TM Datas obtained in 1994, 1997 and 2003 and supported with field observation in 2003. Analyzed was conducted by using of Er Mapper 5.5 with RGB 542 bands. This research revealed that the decrease of regions covered by vegetation was observed from 1994 to 2003. The width of this area in 1994 was 2039.50 ha, while in 1997, this area became 1375.97 ha and decreased to 282.26 ha in 2003. The reduce of this region caused, undoubtedly, the shrink of areas covered by flood around lake site. In fact, this research showed the decrease of this flood area from 627.34 ha in 1994, and became 160.67 ha in 1997 and 44.29 ha in 2003. This reduction of vegetation area was probably due by high intensity of deforestation by resident who changed this area to became paddy rice or other types of land culture. This deforestation was intensified by road construction from Nakau to Air Sebakul in 1990 that split this area.